How the COVID-19 pandemic has affected mental health and internet addiction in adolescents: a comprehensive review - Pjevač, Ana; Safiye, Teodora; Biševac, Emir; Mahmutović, Elvis; Jovanović, Mirjana (Archives of Pharmacy, 2024)
The COVID-19 pandemic began in China in December 2019, from where it spread throughout the world and caused a serious threat to both physical and mental health. People were afraid due to COVID-19 cases rapidly increasing all over the world and the quick changes in how people lived. Previous studies have clearly linked the pandemic with signs of depression, stress, anxiety, and suicide thoughts, as well as with excessive internet use. This paper provides a comprehensive review of the available scientific findings regarding the impact of the COVID-19 pandemic on mental health and internet addiction in adolescents. Having insight into the scientific literature on COVID-19, mental health, and internet addiction, we have concluded that during the COVID-19 pandemic time spent on the internet increased due to reduced social activities, which consequently led to internet addiction and thus to psychological distress, increased loneliness, and depression in adolescents. Early intervention is essential to reduce internet addiction and preserve the mental health of adolescents, especially in conditions of increased social stress due to the COVID-19 pandemic.
Keywords: mental health; internet addiction; COVID-19; adolescents